Rechallenge after anti-tuberculosis drug-induced liver injury in a high HIV prevalence cohort - Muhammed Shiraz Moosa; Gary Maartens; Hannah Gunter; Shaazia Allie; Mohamed F. Chughlay; Mashiko Setshedi; Sean Wasserman; David F. Stead; Karen Cohen (AOSIS, 2022)
Background: There are limited data on the outcomes of rechallenge with anti-tuberculosis therapy (ATT) following anti-tuberculosis drug-induced liver injury (AT-DILI) in a high HIV prevalence setting. Objectives: To describe the outcomes of rechallenge with first-line ATT. Method: Hospitalised participants with AT-DILI who were enrolled into a randomised controlled trial of N-acetylcysteine in Cape Town, South Africa, were followed up until completion of ATT rechallenge. We described rechallenge outcomes, and identified associations with recurrence of liver injury on rechallenge (positive rechallenge). Results: Seventy-nine participants were rechallenged of whom 41 (52%) were female. Mean age was 37 years (standard deviation [s.d.] ±10). Sixty-eight (86%) were HIV-positive, of whom 34 (50%) were on antiretroviral therapy (ART) at time of AT-DILI presentation. Five participants had serious adverse reactions to an aminoglycoside included in the alternate ATT regimen given after first-line ATT interruption: acute kidney injury in three and hearing loss in two. The median time from first-line ATT interruption to start of first-line ATT rechallenge was 13 days (interquartile range [IQR]: 8-18 days). Antiretroviral therapy was interrupted for a median of 32 days (IQR: 17-58) among HIV-positive participants on ART before AT-DILI. Fourteen participants had positive rechallenge (18%). Positive rechallenge was associated with pyrazinamide rechallenge (P = 0.005), female sex (P = 0.039) and first episode of tuberculosis (TB) (P = 0.032). Conclusion: Rechallenge was successful in most of our cohort. Pyrazinamide rechallenge should be carefully considered.